"Get encouraged through failures. Failures are not fearful. We can always start over again": Chinese children's lived experiences of zi zun. Issue 2 (3rd April 2021) - Zhang, Hui; Stapleton, Charles Matthew; Hsueh, Yeh; Sun, Fang
ABSTRACT: Zi zun is an indigenous Chinese experience usually glossed in English as self-respect and self-esteem. Previous research connects zi zun with both the need to defend against those who would wrongfully slander the self for failures and the need to learn from past failures. Interpretative phenomenological analysis was used to co-construct narratives with Chinese children about their experiences of zi zun . Sixteen Chinese school-age children participated in semi-structured interviews. Five themes were identified: (1) dignity and respect, (2) humiliation as a cause of zi zun being hurt, (3) self-defense, (4) self-improvement as reactions to hurt zi zun, and (5) the sociability of those with strong zi zun . Results were interpreted within the perspective of Chinese cultural values, focusing on the ways zi zun is intertwined with both goals of interdependence and autonomy. This study provides implications for educating and caring for young native and immigrant Chinese children.